Pengembangan Metode Role Play Untuk Meningkatkan Kemampuan Berbicara Pada Mata Pelajaran Bahasa Arab - Utari, Ririn Fradina; May, Asmal; Hikmah, Hikmah (INTIFA: Journal of Education and Language, 2024)
This research aims to develop and test the effectiveness of the role play method in enhancing the Arabic speaking skills of junior high school students. The study utilized the classroom action research method conducted in two cycles with students from class. Research instruments in the form of observation sheets and oral tests were employed to measure students' speaking abilities. Data were analyzed descriptively and quantitatively. The research findings indicate that the implementation of the role play method effectively enhances students' speaking abilities. The average score for the oral test in cycle II (75) was higher than that in cycle I (65). Observations also displayed an increase in students' participation and confidence in speaking. This study concludes that the role play method can serve as an effective alternative in learning to enhance the Arabic speaking abilities of students. ABSTRAK Penelitian ini bertujuan untuk mengembangkan dan menguji efektivitas metode role play dalam meningkatkan kemampuan berbicara bahasa Arab siswa SMP. Penelitian ini menggunakan metode penelitian tindakan kelas yang dilakukan dalam dua siklus pada siswa kelas .Instrumen penelitian berupa lembar observasi dan tes lisan digunakan untuk mengukur kemampuan berbicara siswa. Data dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa penerapan metode role play efektif meningkatkan kemampuan berbicara siswa. Nilai rata-rata tes lisan pada siklus II (75) lebih tinggi daripada siklus I (65). Observasi juga menunjukkan peningkatan keaktifan dan keberanian siswa dalam berbicara. Penelitian ini menyimpulkan bahwa metode role play dapat menjadi alternatif pembelajaran yang efektif untuk meningkatkan kemampuan berbicara bahasa Arab siswa